Small Traders’ Construction of People’s Business Credit (KUR) from Bank BRI (A Study at Pasar Tanjung Anyar, Mojokerto) - Yakut Nariyah; Diyah Utami (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the social construction of small traders regarding the KUR BRI program in Tanjung Anyar Market, Mojokerto City. The conditions in the field indicate a discrepancy between the objectives of the KUR program as an effort to address capital constraints and the reality of declining income due to the decreasing number of market visitors. This study employs a qualitative method with an ethnographic approach to understand the meanings constructed by traders based on their experiences and social interactions. The subjects of this study are small traders who have been KUR BRI customers for at least one year, selected using a purposive sampling technique. Data were collected through interviews and field observations, then analyzed using the Miles and Huberman model. The results of this study show that the social construction of traders is formed through three processes: externalization, objectification, and internalization. The KUR program is interpreted not only as government financial assistance but also as an economic burden amid declining market conditions. Social factors such as networks, trust, and experience also influence traders’ economic decisions. This study demonstrates that economic reality is not merely rational but is also socially constructed in the everyday lives of traders.